1984
DOI: 10.1037/0022-3514.46.2.357
|View full text |Cite
|
Sign up to set email alerts
|

Mood influences on helping: Direct effects or side effects?

Abstract: A review of the literature concerning the promotive influence of experimentally generated happiness and sadness on helping suggested that (a) increased helping among saddened subjects is an instrumental response designed to dispel the helper's negative mood state, and (b) increased helping among elated subjects is not an instrumental response to (maintain) the heightened effect but is a concomitant of elevated mood. A derivation from this hypothesis-that enhanced helping is a direct effect of induced sadness b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
2
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(207 citation statements)
references
References 39 publications
7
194
2
4
Order By: Relevance
“…Negative mood presumably depleted the resources needed to cope with the information regarding the health risks of caffeine consumption, leading high caffeine consumers to focus on the health benefits of caffeine consumption, perhaps in an attempt to improve their mood (see Clark & Isen, 1982;Isen & Simmonds, 1978;Manucia et al, 1984;Morris & Reilly, 1987;Wegener & Petty, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Negative mood presumably depleted the resources needed to cope with the information regarding the health risks of caffeine consumption, leading high caffeine consumers to focus on the health benefits of caffeine consumption, perhaps in an attempt to improve their mood (see Clark & Isen, 1982;Isen & Simmonds, 1978;Manucia et al, 1984;Morris & Reilly, 1987;Wegener & Petty, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Participants undergoing premenstrual stress in a Zillman (1988) study, for example, favored watching comedy programs on TV. Similarly, the increased tendency to help, observed under both positive and negative mood states, is presumably due to the good feelings that result from such behavior (Manucia et al, 1984;Schaller & Cialdini, 1990). Studies have found support for mood management in the context of information processing as well.…”
Section: Mood Management and Informational Value Of Moodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, what about negative affect? Of interest, negative moods such as sadness or guilt have also been shown to promote helping-for example, when the helping promises to improve mood (e.g., Manucia, Baumann, & Cialdini, 1984), when the person in need calls attention to his or her plight (McMillen et al, 1977), when the negative mood does not lead to self-preoccupation (Kidd & Marshall, 1982), or when individuals feel they have harmed someone (Salovey, Mayer, & Rosenhan, 1991). Thus, researchers have argued that positive moods lead to helping under the majority of circumstances, whereas negative moods lead to helping only under certain conditions-namely, when the rewards of helping are high and the costs are low (e.g., Cunningham, Shaffer, Barbee, Wolff, & Kelley, 1990).…”
Section: Prosocial Behaviormentioning
confidence: 99%
“…For example, Cialdini and colleagues' concomitance theory proposes that positive emotions may not prompt helping behaviors directly, but rather indirectly via the byproducts of positivity, such as liking others more, believing good things will happen in the future (and thus resources can be shared in the present), having an enhanced sense of self-control, and recalling the rewards of past good deeds (Cialdini, Kenrick, & Baumann, 1982;Manucia, Baumann, & Cialdini, 1984). Hence, to the extent that positive triggers enhance positive emotions, they can set off prosociality via multiple indirect mechanisms that are activated by positive emotions.…”
Section: Positive Activity Triggers and Prosocial Effortmentioning
confidence: 99%